The Community Health Response Team: a culturally and linguistically tailored community response to COVID-19 addressing barriers to testing and vaccinations for refugee, immigrant and migrant communities in Atlanta, Georgia - Bekele, Feven; Yu, Kimberly; Archbold, Sam; Mann, Erin; Dawson-Hahn, Elizabeth; Aziz, Omar (Frontiers in Public Health, 2024)
The International Rescue Committee (IRC) in Atlanta and Community Organized Relief Effort (CORE) established a Community Health Response Team in May 2020. The team members represented refugee, immigrant and migrant populations and had expertise in health care and public health. These 18 individuals were recruited from IRC Atlanta's Career Development program, had a variety of backgrounds and spoke 20 languages. They implemented a community-centered COVIDresponse intervention model of pairing education and outreach efforts with testing and vaccination clinics. Due to their team makeup, the Community Health Response Team conducted tailored outreach and education that was culturally and linguistically congruent with their target communities.They administered over 16,000 COVID-19 tests at mobile community sites within the first six months. Once COVID-19 vaccinations were available, the Community Health Response Team coordinated a total of 834 vaccination events in communities with a high number of refugees and in partnership with refugee-and immigrant-trusted community-based organizations, resulting in 31,888 vaccinations. Hiring staff from refugee, immigrant and migrant populations created a sustainable staffing model. Also, embedding culturally specific strategies in their model of pairing education and outreach led to long-term relationships and greater trust with community members. This approach of